Islamic Educational Values in the Empowerment of MSMEs at Masjid Jogokariyan: Reviving the Mosque as a Center of Community Prosperity - Risky, Abu; Suyadi, Suyadi; Masruri, Siswanto; Wantini, Wantini; Bustam, Betty Mauli Rosa (Unisia, 2025)
This study explores the integration of Islamic educational values into the empowerment of Micro, Small, and Medium Enterprises at Masjid Jogokariyan and examines its relevance to mosque prosperity. Recognizing the mosque as a central institution in Islamic civilization—not only spiritually but also socially and economically—this research seeks to understand how values such as honesty, trust, responsibility, independence, and cooperation are internalized within community-based economic development. Employing a qualitative phenomenological approach, data were collected through interviews, participant observation, and document analysis to uncover the lived experiences of mosque leaders and local entrepreneurs. The findings reveal that Masjid Jogokariyan has effectively cultivated an Islamic ethical business culture by embedding spiritual teachings into practical training, promoting transparent financial management, and encouraging inclusive participation through community-driven leadership models. The mosque utilizes structured initiatives such as value-based mentoring, interest-free loan schemes, and “Business Qur’an Circles” to enhance both personal development and economic resilience among participants. These efforts have not only improved the livelihood of local residents but also strengthened congregational engagement, with a significant rise in mosque attendance and communal trust. The empowerment of Micro, Small, and Medium Enterprises has thus become a catalyst for broader mosque prosperity, affirming its role as a dynamic center of learning, service, and transformation. This research underscores the importance of reviving mosque-based Islamic education as a foundation for sustainable community empowerment in contemporary Muslim societies.